Failure properties of ascending thoracic aortic aneurysms with dysfunctional tricuspid aortic valves. (1st August 2021) - Sokolis, Dimitrios P; Angouras, Dimitrios C
Abstract:  : OBJECTIVES: Ascending thoracic aortic aneurysms (ATAAs) often coexist with dysfunctional tricuspid aortic valves (TAVs). How valvular pathology relates to the aortic wall mechanical properties requires detailed examination. METHODS: Intact-wall and layer-specific mechanical properties from 40 and 21 patients with TAV-ATAAs, respectively, were studied using uniaxial tensile testing, longitudinally and circumferentially. Failure stress (tensile strength), failure stretch (extensibility) and peak elastic modulus (stiffness) measurements, along with histological assays of thickness and elastin/collagen contents, were compared among patients with no valvular pathology (NVP), aortic stenosis (AS) or aortic insufficiency (AI). RESULTS: Intact-wall stiffness longitudinally and medial strength and stiffness, in either direction, were significantly lower in AI patients than in AS and NVP patients. Intact-wall/medial thickness and extensibility in either direction were significantly lower in AS patients than in AI and NVP patients. In contrast, intact-wall/medial stiffness circumferentially was significantly higher in AS patients than in NVP patients, consistent with the significantly increased medial collagen in AS patients. Failure properties and medial thickness and elastin/collagen contents were significantly lower (more impaired) in females. The left lateral was the thickest quadrant in NVP patients, but the 4 quadrants were equally thick in AS and AI patients. There were significant differences in strength and stiffness among quadrants, which varied however in the 3 patient groups. CONCLUSIONS: The aortic wall load-bearing capacity was impaired in patients with ATAA in the presence of TAV stenosis or insufficiency. These findings lend biomechanical support to the current guidelines suggesting lower thresholds for elective ascending aorta replacement in cases of aortic valve surgery. Abstract : Ascending thoracic aortic aneurysms (ATAAs) are potentially lethal, with a linearized mortality rate of 1.99% per patient-year [1].